The many facets of disseminated parenchymal brain cysticercosis: A differential diagnosis with important therapeutic implications. - Oscar H Del Brutto (Public Library of Science (PLoS), 2021)
Neurocysticercosis (NCC), the infection of the nervous system by the cystic larvae of Taenia solium, is a highly pleomorphic disease because of differences in the number and anatomical location of lesions, the viability of parasites, and the severity of the host immune response. Most patients with parenchymal brain NCC present with few lesions and a relatively benign clinical course, but massive forms of parenchymal NCC can carry a poor prognosis if not well recognized and inappropriately managed. We present the main presentations of massive parenchymal NCC and their differential characteristics.